ANALYSIS OF THE IMPLEMENTATION OF ISAK 16 - SERVICE CONCESSION AGREEMENTS AND ITS IMPLICATIONS FOR THE COMPANY'S FINANCIAL STATEMENTS - Isnandi, Yedi; Riyadi, Sugeng (Dynamic Management Journal, 2024)
This research is qualitative research with data collection techniques through literature studies and field studies. Literature studies were obtained from scientific journals, accounting standards, government regulations, agreements and business studies related to the implementation of light rail/Light Rail Transit, while field studies were carried out through interviews with informants who understand the implementation of light rail/LRT. The company that is the object of research is PT Jakarta Propertindo (Perseroda) which is a company assigned by the DKI Jakarta Provincial Government to provide infrastructure and facilities for Light Rail Transit Corridor 1 Phase 1 (Kelapa Gading Velodrome). The aim of the research is to analyze appropriate accounting policies for companies related to the Light Rail Transit Infrastructure and Facilities Agreement for Corridor 1 Phase 1 (Kelapa Gading Velodrome) which is the scope of ISAK -16 Services Concession Agreement, implementation of ISAK 16 and implications of implementing ISAK 16 to the financial statements. The results of the research conclude that accounting policies related to the Implementation of Light Rail Transit Infrastructure are within the scope of ISAK 16: Service Concession Agreements so that the implications for financial statements are that companies must record LRT Infrastructure Assets as Intangible Assets, while for the Operation of Light Rail Transit Facilities Rail Transit is within the scope of PSAK 16: Fixed Assets so companies must record LRT Facilities Assets as Fixed Assets.